Ethical Issues in Cochlear Implant Surgery: An Exploration into Disease, Disability, and the Best Interests of the Child - Grodin, Michael A (Kennedy Institute of Ethics journal, 1997)
, This paper examines ethical issues related to medical practices with children and adults who are members of a linguistic and cultural minority known as the DEAF-WORLD. Members of that culture characteristically have hearing parents and are treated by hearing professionals whose values, particularly concerning language, speech, and hearing, are typically quite different from their own. That disparity has long fueled a debate on several ethical issues, most recently the merits of cochlear implant surgery for DEA children. We explore whether that surgery would be ethical if implants could deliver close to normal hearing for most implanted children, thereby diminishing the ranks of the DEAF-WORLD. The ethical implications of eugenic practices with the DEA are explored, as are ethical quandaries in parental surrogacy for DEA children, and their parallels in transracial adoption.